Evidence of pulmonary arterial hypertension in two patients with common variable immunodeficiency. (1st April 2020) - Huston, Jessica; Johnson, Joyce; Hemnes, Anna; Pugh, Meredith
Abstract : Common variable immunodeficiency is a chronic illness plagued with recurrent infections and the potential to develop autoimmune disease. These patients may manifest a spectrum of complications ranging from hematologic malignancy to chronic parenchymal lung disease. Regular immunoglobulin replacement therapy improves immunologic debility but does not mitigate other features of this disease. Here, we discuss a complication of common variable immunodeficiency not previously characterized in the literature. We present two cases of advanced pulmonary vascular disease associated with common variable immunodeficiency treated with pulmonary vasodilators.